The Influence of Principal Performance and Teacher Work Discipline in Increasing the Quality of Education - Zahara Zahara; Elperida Juniarni Sinurat (Graduate School of Universitas Negeri Malang, 2023)
The purpose of this study was to investigate how teachers' work discipline and the principal's performance at SMP Negeri 3 Bireuen contribute to an improvement in education quality. The authors used qualitative methods in this study. The results of the study found that there were 3 roles of the principal in SMP Negeri 3 Bireuen that affected the quality of education, the first was that the principal coordinated all employee staff and also the teacher council in carrying out activities, involving all components, explaining the goals to be achieved, forming committees, conduct monitoring and hold deliberations before carrying out activities. Second, the Principal conducts performance evaluations, compares actual performance with targets, holds monthly meetings, sets specific performance standards, provides rewards and punishments, giving directions to employees, asking for reports after activities and always providing motivation to employee staff and the teacher council. Third, the Principal makes continuous improvements, supervises every semester, provides training and education to teachers and staff, conducts student tutoring during off-school hours and works closely with parents of students. As a result, the principal's performance as a leader can improve the quality of education at SMP Negeri 3 Bireuen. In the meantime, SMP Negeri 3 Bireuen's education quality is also impacted by teacher discipline's impact on education quality.